Determinants of Tax Avoidance with Profitability as a Moderating Variable - Sri Wahyuni; Ani Kusbandiyah; Tiara Pandansari; Anindita Maya Pratita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test the influence of sales growth, leverage and transfer pricing on tax avoidance with profitability as a moderating variable. The population in this research is mining sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling method used purposive sampling which resulted in 165 samples from 63 companies. The results of this research show that sales growth have an positive effect on tax avoidance and transfer pricing have an negative effect on Tax Avoidance. Leverage has no effect on tax avoidance. This study found empirical evidence that Profitability strengthens the influence of the Leverage and Transfer Pricing variables on tax avoidance. Profitability weakens the influence of the sales growth on tax avoidance. Keywords: Tax Avoidance; Sales Growth; Leverage; Transfer Pricing; Profitability.